Tanāzul Ḥaqq: A Strategy for Islamic Banks to Maintain Competitiveness Deposits in the Profit-Sharing System - Aminuddin Busairi (International Journal of Nusantara Islam, 2026)
This study examines the strategic role of Tanāzul Ḥaqq (voluntary relinquishment of rights) as a mechanism that enables Islamic banks to enhance competitiveness within the profit-sharing system. Islamic banks continue to face structural challenges due to competition with conventional institutions that offer fixed and predictable returns, particularly to corporate and institutional clients. This research aims to analyze the fiqh foundations, strategic benefits, and potential risks of Tanāzul Ḥaqq within the context of modern Islamic banking. This research employs a qualitative, library-based method, drawing on classical and contemporary fiqh literature, DSN-MUI fatwas, OJK regulations, Islamic banking reports, and relevant academic studies. A descriptive-analytical approach is applied to evaluate both the Sharīʿah basis and strategic implications of Tanāzul Ḥaqq. The study finds that Tanāzul Ḥaqq is permissible when the waived right has fully materialized, is voluntary, does not alter the essence of the contract, and avoids elements of gharar and riba-like manipulation. Strategically, Tanāzul Ḥaqq enhances product attractiveness, stabilizes bank income, increases operational flexibility, and strengthens customer loyalty. Nevertheless, it carries risks such as information asymmetry, bargaining power imbalance, and potential deviation from the principle of fairness. The effective application of Tanāzul Ḥaqq requires maximum transparency, strong risk governance, and proactive customer education to maintain Sharīʿah compliance and market competitiveness. Originality/Value: This study integrates fiqh analysis with strategic management perspectives, offering a comprehensive framework for implementing.